OzoNews Volume XX - 15 April 2020 - United Nations Environment Programme (2020)
In this issue: -- UNEP’s Statement on the COVID-19 global pandemic -- 1. OzonAction’s iPIC system helps prevent an illegal shipment of 72 tonnes of HCFC-22 2. UNEP OzonAction Encourages Everyone to Celebrate World Refrigeration Day 2020 3. Message from the UN Environment, Ozone Secretariat on COVID-19 4. Upgrades to the Ozone Secretariat website 5. Unusual ozone hole opens over the Arctic 6. Long phased-out refrigeration and insulation chemicals still widely in use and warming the climate 7. 2020 Asia Environmental Enforcement Awards 8. Coronavirus doesn’t stop RAC training: first of its kind experience of online F-Gas training and certification connect Qatar and Italy 9. U.S. Appeals Court in D.C. restores limitations on super-polluting HFCs 10. The California Air Resources Board announced recipients of the 2019 Haagen-Smit Clean Air Awards 11. NASRC announces new incentives program for natural refrigerants 12. ASHRAE Offers Course on the Role of HVAC Systems on Infection Control 13. Prepare for the trend of flammable refrigerants in commercial refrigeration - Webinar 14. How to work safely in times of Covid-19: Useful tips for RAC technicians